Understanding the inter-domain presence of research topics in the computing discipline - DATTA, Subhajit (Institutional Knowledge at Singapore Management University, 2021)
The very nature of scientific inquiry encourages the flow of ideas across research domains in a discipline. Research topics with higher inter-domain presence tend to attract higher attention at individual and organizational levels. This is more pronounced in a discipline like computing, with its deeply intertwined ideas and strong connections with technology. In this paper, we study corpora of research publications across four domains of the computing discipline – covering more than 150,000 papers, involving more than 200,000 authors over 55 years and 175 publication venues – to examine the influences on inter-domain presence of research topics. We find statistically significant evidence that higher collective eminence of researchers publishing on a topic is related to lower inter-domain presence of that topic, fewer authors publishing on a topic relate to the topic being likely to have higher inter-domain presence, while topics belonging to more close-knit clusters of topics are likely to have lower inter-domain presence. Our results can inform decisions around defining and sustaining research agendas and offer insights on the progression of the computing discipline.